2011
DOI: 10.3390/ijms12118146
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Ethyl Acetate Fraction of Sargassum muticum against Ultraviolet B–Irradiated Damage in Human Keratinocytes

Abstract: The aim of this study was to investigate the cytoprotective properties of the ethyl acetate fraction of Sargassum muticum (SME) against ultraviolet B (UVB)-induced cell damage in human keratinocytes (HaCaT cells). SME exhibited scavenging activity toward the 1,1-diphenyl-2-picrylhydrazyl radicals and hydrogen peroxide (H2O2) and UVB-induced intracellular reactive oxygen species (ROS). SME also scavenged the hydroxyl radicals generated by the Fenton reaction (FeSO4 + H2O2), which was detected using electron spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
3
17
0
Order By: Relevance
“…The extracts had no protective effect on lipid peroxidation caused by H2O2. TBARS and AAPH assays evaluate different antioxidant mechanisms; for this reason, some compounds may show antioxidant capacity in both assays (Inayatullah et al, 2012), whereas others show ROS scavenging capacity in the AAPH assay but no anti-peroxidative effect on lipids in the TBARS assay (Piao et al, 2011). Our results indicate that the antioxidant effect of the extracts is mediated by radical scavenging, but not by protecting lipids from peroxidation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The extracts had no protective effect on lipid peroxidation caused by H2O2. TBARS and AAPH assays evaluate different antioxidant mechanisms; for this reason, some compounds may show antioxidant capacity in both assays (Inayatullah et al, 2012), whereas others show ROS scavenging capacity in the AAPH assay but no anti-peroxidative effect on lipids in the TBARS assay (Piao et al, 2011). Our results indicate that the antioxidant effect of the extracts is mediated by radical scavenging, but not by protecting lipids from peroxidation.…”
Section: Discussionmentioning
confidence: 74%
“…Extracts of algae of Ulva and Sargassum spp. genres have been previously described as antioxidants (Shalaby, 2011;Piao et al, 2011). Furthermore, the ability of Ulva lactuca to adsorb heavy metals has attracted industrial interest (Areco et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Extracts derived from S. muticum demonstrate antioxidant, antimicrobial, and anti-inflammatory properties (Kim et al, 2007;Yoon et al, 2010). Previous work by our group revealed that an ethyl acetate fraction of S. muticum (SME) defended human HaCaT keratinocytes against UVB exposure by enhancing cellular antioxidant systems (Piao et al, 2011). However, the molecular mechanism underlying the action of SME was not elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…We previously showed that UVB exposure increases apoptosis in human HaCaT keratinocytes (Piao et al, 2011). Therefore, the UVB-absorbing capacity of SME was first examined using an UV/visible light spectrophotometry.…”
Section: Sme Absorbs Uvb Radiationmentioning
confidence: 99%
See 1 more Smart Citation